ANALISIS SOSIOLOGI TERHADAP WARISAN BUDAYA DAN IDENTITAS LOKAL BATIK SANGIRAN - Triesanto Romulo Simanjuntak; Rizki Amalia Yanuartha; Tunjung Wijanarka; Putri Hergianasari (Universitas Halu Oleo (UHO), 2023)
This study analyzes the phenomenon of Sangiran Batik in Central Java, Indonesia, from a sociological perspective with a focus on cultural heritage and local identity. Sangiran batik has a deep meaning for the local people and is an important part of Central Java's cultural heritage. This study aims to understand the role of Sangiran Batik in shaping and maintaining the cultural identity of the local community and the resulting social impact. The research method used is a qualitative approach through in-depth interviews with batik artisans, local communities and cultural observers. From the data analysis it was found that Sangiran Batik has a significant role in shaping the cultural identity of the local community. Batik cloth is a symbol of the richness of local culture and history, connecting the younger generation with ancestral heritage. In addition, the production and promotion activities of Sangiran Batik also have a positive economic and social impact on the local community.